Mengatasi Kesulitan Belajar Siswa SMK Melalui Pengembangan Video Pembuatan Saku Pada Elemen Teknik Dasar Menjahit SMK N 1 Ranah Pesisir - Ningsih, Tri Osvira; Nelmira, Weni (Jurnal Ilmiah Dikdaya, 2024)
This research is based on the background of the problems contained in learning elements of Basic Sewing Techniques in pocket making material, where students have difficulty understanding the steps and techniques for practical pocket making. This research aims to produce learning media in the form of videos that are valid and practical so that they can be used as a learning resource by students in learning pocket-making material. This research is development research or what is known as Research and Development (R&D) by applying the 4D model. The data collection techniques for this research are observation, interviews and questionnaires. This video was tested for validity by 3 media and material expert validators as well as a practicality test seen from the responses of the teacher who supervised the Basic Fashion Skills subject and Class X Fashion Design students, namely, 12 small group students and 32 large group students. The research instrument used an assessment sheet in the form of a questionnaire which was analyzed using a Likert scale. The analysis technique used is quantitative descriptive data analysis. The results of the validity test for media experts obtained a score of 84.8%, while the validity of material experts obtained a score of 91.8%, so that a total score of 88.3% could be obtained in the very valid category. Furthermore, a practicality test was carried out by the subject supervisor, obtaining a score of 99%, and the results of the practicality test for small group students obtained a score of 94.06%. Then the practicality test results of the large group of students obtained a score of 93.53%, so that a total score with a percentage of 95.53% could be obtained in the very practical category. It can be concluded that this video media is said to be feasible and practical and can be used as a learning medium.